2017
DOI: 10.3762/bjoc.13.44
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization reactions of aryl selenophen-2-yl-substituted thiocarbonylS-methanides as diradical processes: a computational study

Abstract: An intriguing stepwise diradical mechanism of the dimerization of the reactive intermediate (thiocarbonyl S-methanide) appearing in the reaction of phenyl selenophen-2-yl thioketone with diazomethane was studied by means of computational methods. The preferred formation of the unusual macroheterocycle, competitive with the 1,3-ring closure leading to a thiirane and the head-to-head dimerization yielding a 1,4-dithiane derivative, respectively, was explained based on the analysis of the structure of the favored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…The studies showed that the presence of a heteroaryl substituent strongly modifies the reactivity of the thioketones. For example, the reaction of phenyl selenophen-2-yl thioketone (4a) with diazomethane (5) led to the 14-membered cyclodimer 7 of the intermediate thiocarbonyl S-methanide 6 via a biradical mechanism [20,21] (Scheme 2).…”
Section: Scheme 1 Methods For Generation Of Nitriliminesmentioning
confidence: 99%
“…The studies showed that the presence of a heteroaryl substituent strongly modifies the reactivity of the thioketones. For example, the reaction of phenyl selenophen-2-yl thioketone (4a) with diazomethane (5) led to the 14-membered cyclodimer 7 of the intermediate thiocarbonyl S-methanide 6 via a biradical mechanism [20,21] (Scheme 2).…”
Section: Scheme 1 Methods For Generation Of Nitriliminesmentioning
confidence: 99%
“…[20] The formation of the latter was explained via a stepwise mechanism with the intermediacy of a delocalized diradical species, and this interpretation was supported by an independent computational study. [21] The (3+2) cycloaddition reactions with alkyl and trimethylsilyl-substituted diazomethanes with hetaryl thioketones were also postulated to follow a stepwise mechanism. [22] The goal of the present study was the elucidation of the reaction mechanism of the model (3+2) cycloadditions of selected diaryl thioketones 3a-c with diphenyldiazomethane (2b) by means of computational methods.…”
Section: Introductionmentioning
confidence: 99%
“…These [3+2]cycloadducts extrude N 2 upon warming and reactive thiocarbonyl S-methanides are generated thereby [1][2][3]. In recent publications we demonstrated that hetaryl thioketones react with diazomethane with immediate evolution of N 2 already below 70ºC [4,5]. In these reactions, delocalized diradicals were postulated as intermediates, which either undergo dimerization or trap the starting thioketone to give 4,4,5,5-tetrasubstituted 1,3dithiolanes in a regioselective manner.…”
Section: Introductionmentioning
confidence: 99%